An Economics Pocket Book on Financial Literacy for Tenth Grade Students - Yunita Sulastri (Jurnal Pendidikan Indonesia, 2026)
The availability of relevant, practical, and easy-to-understand teaching materials is an important requirement in supporting the learning process, especially in financial literacy material. The main problem in this study is the unavailability of concise teaching materials that can help 10th grade students understand the basic concepts of personal financial management in a simple and applicable manner. This study aims to develop, validate, and produce a financial literacy pocketbook that is suitable for use as a medium for economics learning. This type of research is Research and Development (R&D) using the ADDIE model. The research subjects included material experts, media experts, economics teachers, and 10th grade students. Research data were obtained through validation sheets, teacher response questionnaires, and trials with students. The developed pocketbook contains basic financial literacy materials, such as money management, needs and wants, priority scales, saving, and simple financial decision-making. The results showed that the financial literacy pocketbook received a very decent rating from the validator and received very positive responses from teachers and students. The implications of this study indicate that pocketbooks can be used as an effective, interesting, and practical supplementary learning resource in helping students understand financial literacy and ready to be used in economics learning.